Pendampingan dalam Meningkatan Motivasi dan Minat Anak dalam Menghafal Al-Qur an Juz 30 Melalui Kegiatan Lomba sambung ayat di Desa Kerpangan Probolinggo - Maghfiroh, Eva; Farid, Achmad; Hidayatullah, Indra (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
It is important to create a supportive environment for children to memorize the Quran. A positive environment, such as support from parents and the community, can increase children's interest in learning and memorizing the Quran. This activity aims to create a fun, competitive atmosphere, so that children are more motivated to memorize the Quran, especially Juz 30. This mentoring program uses a qualitative approach with participatory action research to explore the factors that influence children's motivation and interest in memorizing. The results of this activity are expected to shape a generation that loves the Quran and has noble morals, as well as strengthen social support from family and community.